Analysis of the Determining Factors for Educated Unemployment in Banten: A 2024 Sakernas Data Analysis - Mulya, Ziddan Baasith; Susilo (Journal of Development Economic and Social Studies, 2026)
Educated unemployment remains a critical issue in Indonesia’s labor market, particularly in Banten, which consistently records high unemployment rates. This study aims to analyze individual-level factors influencing the probability of becoming an educated unemployed worker using data from the August 2024 Sakernas. A binary logistic regression was applied to 6,951 respondents with at least a senior high school education. The results indicate that age significantly increases the likelihood of unemployment, while work experience strongly reduces it. Women are nearly four times more likely to be educated unemployed. Educational attainment at the SMA, SMK, and Diploma levels also increases unemployment risk compared to postgraduate graduates, whereas the bachelor’s degree category is not statistically significant. Training participation, ICT literacy, and living in urban significantly reduce unemployment probability. Additionally, using Prakerja subsidies for business capital substantially decreases unemployment risk. These findings highlight that educated unemployment in Banten is shaped by demographic factors, human capital characteristics, and the effectiveness of training programs, underscoring the need for policies that enhance skills quality and align competencies with industry demands.